An analysis of francis poulenc’s composition sonata for clarinet in Bb and piano technical chalengges faced by clarinettist in performing / Azmi Azhar - Azhar, Azmi (2014)
Francis Poulenc is a French Composer and one of the members of Les Six. The influenced of his composition is changing and his has his own stylistic era. The Sonata for Clarinet in Bb and Piano is one of his last works. This sonata is based on the traditional sonata form and influenced by the neoclassical sonata characteristics, It is written to one of his friends named Arthur Honneger. The sonata is written for Clarinet in Bb and Piano. Therefore, ‘here’s some difficulties has been faced by the clarinettist in order to play this sonata. Confusion on how to deliver the sonata leads to a bad deliverance in performing This study will shows the characteristics of the neoclassical sonata, defining the compositional technique that has been used by Francis Poulenc. and defining the technical difficulties that is occurring in this sonata in term of performing. This research is important as it will also give and ideas about the common and uncommon problems occur while playing this sonata. . It is hoped that will benefit every clarinetlist in all kinds of profession in order to help them to overcome all the issues and deliver the sonata very well. The subjects of this research are limited to only 6 respondents who played this sonata before.